KNOWLEDGE, ATTITUDE, AND PRACTICE OF EMERGENCY CONTRACEPTION AMONG HARAMAYA UNIVERSITY FEMALE STUDENTS; EASTERN ETHIOPIA - Desta, Berhanu (Ethiopian Journal of Reproductive Health, 2018)
Abstract Background: An estimated 10-40% of young, unmarried women experience unwanted pregnancies. Many of these can be prevented by using emergency contraception (EC). Objective: To assess the knowledge, attitude, and practice of EC. Methods: A cross-sectional survey was conducted on 572 female students of Haramaya University in March 2009. Data was collected using a structured questionnaire. Participants were selected through multistage sampling technique. To analyze the data, frequency distribution and logistic regression were used. Results: 272(47.6%) of respondents have even heard of EC. Of these, 70(25.7%) had good knowledge and 208 (76.5%) had favorable attitude. About (17(48.7%) of respondents had ever used EC pills. Logistic regression model identified age, previous residence; religion, grade level, sexual experience, media exposure, sex education, currently chewing chat, and currently taking alcohol are associated with awareness of EC. Similarly, age, religion, and sex education were found to be associated with favorable attitude. Conclusion: The specific knowledge and practice of EC was low. Therefore, to enhance EC knowledge and practice among female students, Haramaya University needs to design and include a reproductive health course in its curriculum and offer to all students as a common course. Ethiopian Journal of Reproductive Health, 2011, 5(1): 10-21